Microenvironmental Factors Modulating Tumor Lipid Metabolism: Paving the Way to Better Antitumoral Therapy - Cai, Limeng; Ying, Minfeng; Wu, Hao (Frontiers in Oncology, 2021)
Metabolic reprogramming is one of the hallmarks of cancer and is driven by both the oncogenic mutations and challenging microenvironment. To satisfy the demands of energy and biomass for rapid proliferation, the metabolism of some substrates and nutrients in tumor cells undergoes important changes, especially glucose and glutamine. Aberrant lipid metabolism has also gained increasing attention in facilitating tumor development and metastasis in the past few years. But obstacles emerged in the application of targeting lipid metabolism in tumor cells due to the lack of cognition on the regulating mechanism. Noteworthy, Tumor cells closely interact with adjacent stroma, which highly contributes to metabolic rewiring of critical substrates in cancer cells. This fact makes the impact of microenvironment on tumor lipid metabolism a topic of renewed interest. Abundant evidence has proved that various factors existing in the tumor microenvironment can rewire multiple intracellular signaling pathways and proteins involved in lipid metabolic pathways of cancer cells. Here, we focus on unraveling underlying microenvironmental factors that regulate the tumor lipid metabolism, with the aim to correlate altered lipid profiles with changing milieu and to better explore the potential of lipid metabolism as an anticancer approach.